PENINGKATAN KAPASITAS PEREMPUAN PESISIR DI PANTAI CEMARA KABUPATEN LOMBOK BARAT - Hafizah Awalia; Arif Nasrullah; Farida Hilmi (Politeknik Negeri Sriwijaya, 2023)
Abstract Coastal women in Cemara Beach experience various kinds of problems and obstacles in increasing their capacity, including limited opportunities for access to education and training, lack of economic capital, vulnerable employment, changes in the social and cultural environment that require women to have the capacity to manage resources, lack of access to government and lack of knowledge about gender mainstreaming. This community service was carried out in the Cemara Beach Coastal Area, West Lombok Regency, with the target audience being coastal women with various professions, the type of activity in this community service is socialization and counseling. The results obtained from this community service are successful in advocating and bringing together the perspectives of interested parties who can support sustainability in community development, including coastal women, community leaders and the local government. of course, it cannot be separated from the participation of various parties who can support sustainability in community development, including coastal women, community leaders and local government. Keywords: Coastal Women, Capacity, Access, Advocating